Stars and keys : folktales and creolization in the Indian Ocean - Haring, Lee (Indiana University Press, 2007)
The culture of Madagascar, Mauritius, Seychelles, Reunion, and the Comoros is a blend of traditions that have been brought from Africa, South Asia, Europe, and Middle East. This work features folktales from these islands that reflect their cultural diversity and gives an opportunity to see the fluidity of traditions and process of creolization.